Influence of guide support on the accuracy of static Computer-Assisted Implant Surgery (sCAIS) in partially edentulous cases using a keyless guiding system: an in vitro study - David Kasradze; Ricardas Kubilius (BMC Oral Health)
Abstract Purpose To evaluate the influence of guide support on the accuracy of sCAIS using a keyless guiding system in different cases of partial edentulism. Methods Sixty polyamide models of partially edentulous maxillae, simulating anterior and posterior single-tooth gaps as well as anterior and distal extended edentulous areas, were fabricated. Full-arch, 2-teeth, and 4-teeth supported surgical guides were used to place implants at FDI 15, 17, 21, 26 sites in Model A and at FDI 12, 22, 15 sites in Model B. In total, 210 replica implants were placed using 120 surgical guides in seven implantation sites. Three-dimensional crestal and apical, angular and vertical deviations from the planned implant positions were compared using the Kruskal-Wallis H test with Dunn’s procedure for multiple pairwise comparisons. Results Overall median 3D crestal and apical deviations of implants placed with 2-teeth guide support (0.62 mm [0.45–0.84], 0.92 mm [0.69–1.25]) and 4-teeth guide support (0.65 mm [0.52–0.81], 1.01 mm [0.8–1.26]) were significalty lower compared to the full-arch support group (0.86 mm [0.63–0.98], 1.26 mm [0.98–1.52]) with values of p < 0.017. Overall angular and vertical deviations of implants placed with 2-teeth guide support (2.61° [1.71–3.75], 0.32 mm [0.15–0.44]) were significantly lower compare to the full-arch support group (3.22° [2.25–4.41], 0.46 mm [0.24–0.62]). In the subgroup analysis, implants placed at the FDI 12, 22, and 15 positions exhibited significantly higher 3D and angular deviations with full-arch guide support, whereas the 3D apical and angular deviations of were significantly lower with 2-teeth guide support at the FDI 21 site. Conclusions The deviations in all guide support groups did not exceed the recommended safety margins. Statistically significant differences were found between guide support groups, with influence of guide support on the accuracy of sCAIS varying across different implantation sites. Trial registration Not applicable.